Pimpinan yang Memiliki Koneksi Politik Memperkuat Kinerja Profitabilitas terhadap Penghindaran Pajak - Yuli Fitiasari; Suwandi Suwandi (JIATAX (Journal of Islamic Accounting and Tax), 2020)
The purpose of this study is to examine the effect of profitability performance and interaction of political connections with profitability performance on tax avoidance. The sample in this study were all manufacturing companies in the Indonesia Stock Exchange (IDX). The method of determining the sample using purposive sampling in accordance with predetermined criteria and obtained a sample of 63 companies. The analysis technique is multiple linear regression. The test results of multiple linear regression analysis show that profitability performance has a significant effect on tax avoidance, while the interaction of political connections with profitability performance has a significant effect on tax avoidance. Tax avoidance is an effort to alleviate the tax burden by not violating the law. Tax avoidance is a complex and unique issue because it does not violate the law (legal) but is not desired by the government because it reduces state revenues. Political connections that are built by the company will increase the likelihood of companies being involved in tax avoidance activities. Profitability performance is the central key for management who has proximity to officials in making projections that are possible in tax avoidance.